El lenguaraz y la comunicación en la frontera argentina en el siglo XIX - Perna, Carlos Gabriel (2016)
In 1872 the Ranqueles signed a peace treaty with missionaries and military leaders on the frontier-post of the Pampa. This peace treaty will be the last document to regulate the relationship between the Ranqueles, indigenous peoples of Mapuche descent, and the “Christians” in the argentine Pampa until in 1879 argentine troops invade the territory and take possession of it. An analysis of letters and other written documents from this period shows, that in this environment of intercultural communication bilingual persons, lenguaraces, played a major part, even though their participation in the communicational process is not always noted. The lenguaraz had the task to interact between two cultures using his cultural, idiomatic and expressive knowledge. Eugenio Coseriu’s theory of surrounding fields is used here, to analyse how the participation of a translator, explicitly mentioned or omitted, has affected and found influence in the oral texts and written documents.